Monolithic zirconia crowns and fixed partial denture in anterior and posterior regions as a prosthetic solutions (case report) - Ahmed Islam Abourayan; Marwan Aggag (Advances in Medical, Pharmaceutical and Dental Research)
The increase in patient’s demand for an esthetic natural like and a strong functional restoration now days, using of all-ceramic zirconia fixed partial denture for rehabilitation of missing posterior teeth has been increasing in daily dental practice, Although dental implants are the treatment of choice in most of our cases today, but it’s not always executable for all patients due to many reasons such as, chronic smoking, alcoholism, uncontrolled diabetes, and most importantly poor oral hygiene. Monolithic, multilayer zirconia gave the desired mechanical strength that can withstand high masticatory forces, without having a negative effect on its esthetic appearance, which makes it the material of choice in our case.   Received: 14 August 2024 Accepted: 01 September 2024 Published: 18 September 2024